Faces of Anorexia in Adolescents: Diagnosis, Risk, and Support - Skibicka, Julia Natalia; Rosińska, Kamila; Janicka, Ewelina Justyna; Rosiński, Mateusz; Niedźwiedzka, Monika (Quality in Sport, 2025)
Introduction: Anorexia nervosa (AN) is an eating disorder most commonly occurring during adolescence, characterized by the highest mortality rate among mental health conditions. It is a serious disorder affecting the physical and psychological development of children and adolescents. The increase in AN cases following the COVID-19 pandemic and difficulties in its early diagnosis present significant challenges in treatment. Objective: The aim of this paper is to review current research on anorexia nervosa, its symptoms, risk factors, the impact of the COVID-19 pandemic, and the role of social media in the development of this disorder. Therapeutic approaches, with a particular focus on family therapy and psychotherapy, are also discussed. Methods: This study provides a literature review on anorexia nervosa, focusing on its etiology, the impact of the pandemic, and contemporary treatment methods. Available research on co-occurring mental disorders, the effects of social media, and the role of family in the therapeutic process was analyzed. Conclusion: Anorexia nervosa is a serious disorder that requires intensified preventive and diagnostic efforts, especially in young individuals. The COVID-19 pandemic and increased social media activity have significantly exacerbated AN symptoms. Effective treatment necessitates a multifaceted approach, including early diagnosis, family therapy, and psychotherapy. A supportive family evironment can significantly enhance treatment outcomes.